2006
DOI: 10.1143/jjap.45.4960
|View full text |Cite
|
Sign up to set email alerts
|

Frequency Dependence of Drain Conductance due to Hole Accumulation in InAlAs/InGaAs High Electron Mobility Transistors

Abstract: The frequency dependencies of the drain conductance (G d ) and the responsivity of InAlAs/InGaAs high electron mobility transistors were investigated using a network analyzer. The G d exhibited the same frequency dependence as responsivity under 1.3-mm-wavelength laser illumination, indicating that the frequency dependence of G d arises from the recombination of holes that have accumulated in the source region with the two-dimensional electron gas (2DEG). The holes were generated in the drain region by impact … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
22
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
4
1

Relationship

4
1

Authors

Journals

citations
Cited by 9 publications
(24 citation statements)
references
References 25 publications
2
22
0
Order By: Relevance
“…Here, was obtained according to the method described in ref. 12, in which f 3dB is obtained from the experimental data for the frequency dependence of G d and then is calculated using the relation f 3dB ¼ 1=2. For convenience, the effective drain-gate voltage V DG,eff applied to the side of the gate-to-drain path is defined as V DS -V DS,sat following a method reported elsewhere, 2) where V DS,sat is the drain-to-source voltage defined in such a way that d 2 I DS =dV DS 2 is at a minimum.…”
Section: Frequency Dispersion Of G D and Minority-carriermentioning
confidence: 99%
See 1 more Smart Citation
“…Here, was obtained according to the method described in ref. 12, in which f 3dB is obtained from the experimental data for the frequency dependence of G d and then is calculated using the relation f 3dB ¼ 1=2. For convenience, the effective drain-gate voltage V DG,eff applied to the side of the gate-to-drain path is defined as V DS -V DS,sat following a method reported elsewhere, 2) where V DS,sat is the drain-to-source voltage defined in such a way that d 2 I DS =dV DS 2 is at a minimum.…”
Section: Frequency Dispersion Of G D and Minority-carriermentioning
confidence: 99%
“…This result is consistent with that shown in the previous paper. 12) Next, the result for the V GS dependence of will be discussed qualitatively. The concentration of holes generated by impact ionization in the drain region increases with V GS because the concentration of 2DEG injected into the drain region increases with V GS .…”
Section: Frequency Dispersion Of G D and Minority-carriermentioning
confidence: 99%
“…The carrier lifetime of accumulated holes is dominated by the recombination of holes with two-dimensional electron gas (2DEG) [5,6]. Furthermore, we showed that InAlAs/ InGaAs HEMTs have a high responsivity when they are used as optical receivers [7].…”
mentioning
confidence: 99%
“…In addition, the carrier lifetime of accumulated holes is dominated by the recombination of holes with twodimensional electron gas (2DEG) [5,6]. We previously demonstrated that the frequency dependence of drain con-ductance (G d ) is caused by the accumulation of holes in the source region and their recombination with 2DEG.…”
mentioning
confidence: 99%
“…In addition, it was demonstrated that the non-radiative Auger recombination is the dominant mechanism when holes recombine with 2DEG. Furthermore, the minority carrier lifetime due to Auger recombination has been estimated using G d with the effective drain-gate voltage (V DG.eff ) increased [5,6].…”
mentioning
confidence: 99%